(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
In the era of economic and digital globalization, financial data integration is the main key to effective and efficient tax management in companies. The lack of integration between internal financial systems and tax reporting causes data inconsistency, increased risk of reporting errors, and low tax compliance. This study examines in depth the importance of data consolidation in supporting modern tax management, by adopting descriptive qualitative methods through literature studies and case analysis. The results show that companies that implement financial data integration have higher levels of efficiency in tax reporting, better transparency, and significant reductions in compliance costs. These findings also highlight the role of information technology in supporting a more accountable and data-driven tax administration system. This study recommends technology implementation strategies such as ETL, XBRL, and data warehousing to strengthen the tax reporting system, as well as the importance of collaboration between companies and tax authorities to form a transparent and trusted data ecosystem.